RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE IN FORMULA FEEDING WITH CARRIES RAMPAN IN TKIT AL-JANNAH STUDENTS BANDA ACEH CITY - Zahara, Elfi; Mufizarni (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Factors that cause rampant caries in preschool children are the use of formula milk with high carbohydrate content and the habit of consuming formula milk using a milk bottle. This study aims to determine the relationship between mothers' knowledge of formula feeding and rampant caries in students of TKIT Al-Jannah, Banda Aceh City. This type of research is analytic with a cross-sectional design which was carried out on 11 to 14 April 2022, the population and sample in this study used a total population technique of 30 TKIT Al-Jannah students and their mothers . as a respondent. The examination was carried out by interviewing the mother and examining rampant caries in Al-Jannah TKIT students. Univariate data analysis is to determine the frequency distribution of each variable bivariate analysis using chi-square statistical test = 0.05. The results showed that mothers who had poor knowledge of the category with children who experienced rampant caries were 15 students (83.3%). the results of the chi-square test have a p-value of 0.009 (p < 0.05). The results of this study can be concluded that there is a relationship between mothers' knowledge of formula feeding with rampant caries occurrence in TKIT Al-Jannah students. It is recommended for mothers to be able to increase their knowledge of dental and oral health, especially rampant caries.